The roles of atmospheric circulation and sea surface temperature in UK surface climate. (26th October 2022) - Fereday, David; Knight, Jeff
Abstract: Atmospheric circulation has been identified as a key driver of recent extreme seasons in the UK, while local sea surface temperature (SST) also influences UK surface climate. Here, we investigate the roles of atmospheric circulation and SST in driving UK climate, using atmospheric model simulations with constrained global atmospheric circulation and selected SST boundary conditions. These simulations successfully reproduce observed UK‐mean temperature and precipitation. For UK temperature, circulation has a larger effect than SST for all seasons and timescales. SST influence peaks in summer on seasonal timescales. For precipitation, SST influence is weaker and is modulated by circulation. Nevertheless, SST effects provide skilful forecasts of spring and autumn UK temperature, and also contribute to UK temperature extremes in winter and summer. Abstract : Atmospheric circulation is a driver of extreme UK temperature and precipitation events, but local sea surface temperature (SST), itself partly driven by circulation, also plays a role. We use model experiments to investigate the relative impact of circulation and SST on the UK climate, finding that circulation is the dominant factor. However, SST also has an influence: it amplifies circulation‐driven temperature extremes in summer and winter and can also skilfully forecast UK temperature in spring and autumn.